Land Suitability Assessments for The Palm Plantation (Arenga pinnata L.) As Non-Timber Forest Product Using Geographic Information System - Athiyyah Faadhilah Faadhilah; Mahawan Karuniasa; Sri Setiawati Tumuyu (The University of Lampung, 2023)
The use of sugar palm plants as a producer of palm sugar, which is a non-timber forest product (NTFP) is considered not optimal and has the potential to be cultivated. Assessing land suitability is necessary for assessing the potential of land resources to provide information and production values. This study aims to analyze land suitability for sugar palm plantations as measured by climate, land physical properties, and a combination of these parameters. The research was conducted in Baru Ranji Village, Merbau Mataram District, South Lampung Regency, using spatial analysis methods through the use of overlay, matching, and scoring techniques through the Geographic Information System (GIS). The results showed that climatic parameters become limiting factors and only shift the level of land suitability and when combined with the physical parameters, the land was suitable for sugar palm cultivation. The use of agroforestry system in social forestry for sugar palm cultivation can increase economic and environmental conservation value. Keywords: Agroforestry, Conservation, Cultivated, Palm sugar, Social Forestry